2021
DOI: 10.1039/d1tb00689d
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional DNA dendrimer nanostructures for biomedical applications

Abstract: DNA nanomaterials have attracted ever-increasing attentions over the past decades attributing to the incomparable programmability and multifunctionality. In particular, DNA dendrimer nanostructures, as major research focus, have been applied in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 111 publications
0
11
0
Order By: Relevance
“… 291 To prolong the half-life of drugs, dendrimer-based NPs were chosen but were found to be time-consuming to produce, potentially cytotoxic and non-degradable. 292 When encountering insoluble drugs such as HCPT, cyclodextrins have often been chosen to increase the solubility of the drug, but cyclodextrin-based NPs were found to be easily and rapidly cleared in circulation. 293 Nanogels and hydrogels are favored for their excellent biocompatibility, large surface area and adjustable properties, but also have the problem of being easily cleared.…”
Section: Discussionmentioning
confidence: 99%
“… 291 To prolong the half-life of drugs, dendrimer-based NPs were chosen but were found to be time-consuming to produce, potentially cytotoxic and non-degradable. 292 When encountering insoluble drugs such as HCPT, cyclodextrins have often been chosen to increase the solubility of the drug, but cyclodextrin-based NPs were found to be easily and rapidly cleared in circulation. 293 Nanogels and hydrogels are favored for their excellent biocompatibility, large surface area and adjustable properties, but also have the problem of being easily cleared.…”
Section: Discussionmentioning
confidence: 99%
“…Dendrimers are highly ordered, symmetric, branched polymeric molecules. Many reports have shown that dendrimers potentially transfer genes into cells without damaging or deactivating the DNA ( 215 217 ). Poly(amidoamine), or PAMAM, is the most popular dendrimer, which used ethylene diamine or ammonium as a core molecule.…”
Section: Different Immunotherapies and Polymeric Systems Applying For...mentioning
confidence: 99%
“…Dendrimers can also be synthesized from the outside-in using convergent synthesis techniques (J. W. Lee et al, 2006). In addition to PAMAM, common dendrimers in biomedical and biosensor applications include polylysine (Boyd et al, 2006;Kaminskas et al, 2008Kaminskas et al, , 2009, poly(propyleneimine) (Idris et al, 2020;Scherrenberg et al, 1998), poly(carbosilane) (Rabiee et al, 2020), and DNA (L. Liu et al, 2021;Meng et al, 2014;J. Wang et al, 1998).…”
Section: Brush Dendritic and Hyperbranched Polymersmentioning
confidence: 99%